Effect of fentanyl on 5-HT efflux involves both opioid and 5-HT(1A) receptors - Tao, Rui (2003)
1. Fentanyl is a μ-opioid analgesic that might disinhibit 5-HT neurons and thus increase 5-HT efflux. However, fentanyl also binds to 5-HT(1A) receptors, and if it activates 5-HT(1A) somatodendritic autoreceptors, the resultant inhibition might offset opioid-mediated increases in 5-HT efflux. To test this hypothesis, we used microdialysis to study effects of fentanyl on extracellular 5-HT in the dorsal raphe nucleus (DRN) of unanesthetized rats. 2. Systemic administration of fentanyl (0.01–0.2 mg kg(−1), s.c.) increased 5-HT efflux in the DRN. An intermediate dose of fentanyl (0.05 mg kg(−1)) produced the maximum increase in 5-HT to ∼180% of baseline levels in the DRN. Naltrexone (10 mg kg(−1), s.c.) blocked the increase in response to systemic fentanyl (0.05 mg kg(−1)). 3. In contrast, during infusion into the DRN, fentanyl (10–1000 μM) induced a dose-dependent decrease in 5-HT. Naltrexone and nor-binaltorphimine failed to block the decrease suggesting that μ- and κ-opioid receptors did not mediate this effect. 4. Systemic (−)-pindolol (8 mg kg(−1), s.c.) or infusion of WAY-100635 (100 μM) into the DRN blocked the decrease, and instead 5-HT increased in response to local infusion of fentanyl (100 μM). WAY-100635 (0.3 mg kg(−1), s.c.) also potentiated the effect of systemic fentanyl (0.2 mg kg(−1), s.c.). (−)-Pindolol and WAY-100635 block 5HT(1A) receptors, indicating that inhibition of 5-HT neuronal activity resulting from fentanyl binding to somatodendritic autoreceptors attenuated opioid-mediated increases in 5-HT efflux. 5. These results provide novel evidence that besides stimulating μ-opioid receptors, fentanyl is a 5-HT(1A) receptor agonist. Possibly, this contributes to lethality of fentanyl overdose.